2023
DOI: 10.1037/pro0000496
|View full text |Cite
|
Sign up to set email alerts
|

Minimal effect of messaging on engagement in a digital anxiety intervention.

Abstract: This study evaluated the effectiveness of different recruitment messages for encouraging enrollment in a digital mental health intervention (DMHI) for anxiety among 1,600 anxious patients in a large health care system. Patients were randomly assigned to receive a standard message, or one of five messages designed to encourage enrollment: three messages offered varying financial incentives, one message offered coaching, and one message provided consumer testimonials. Patients could then click a link in the mess… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 31 publications
1
4
0
Order By: Relevance
“…In contrast, model-predicted rates of enrollment and starting the first session were relatively similar across message features. While these findings are contrary to hypotheses, they align with prior studies (one with a Latinx sample, and one with a predominantly non-Latinx white sample) that observed small and nonsignificant differences across message conditions in rates of enrollment (less than .01%; Graham et al, 2012;2.74%;Silverman et al, 2023) and starting the first session (3.30%; Silverman et al, 2023). It is not surprising that the message features had the greatest impact at the initial stage of the recruitment process (i.e., clicking the link to visit the DMHI website) rather than subsequent stages (i.e., enrolling and starting the first session) since messages were delivered at this point in the recruitment pipeline.…”
Section: Minimal Effect Of Culturally Informed Message Features (Aim 1)supporting
confidence: 69%
See 4 more Smart Citations
“…In contrast, model-predicted rates of enrollment and starting the first session were relatively similar across message features. While these findings are contrary to hypotheses, they align with prior studies (one with a Latinx sample, and one with a predominantly non-Latinx white sample) that observed small and nonsignificant differences across message conditions in rates of enrollment (less than .01%; Graham et al, 2012;2.74%;Silverman et al, 2023) and starting the first session (3.30%; Silverman et al, 2023). It is not surprising that the message features had the greatest impact at the initial stage of the recruitment process (i.e., clicking the link to visit the DMHI website) rather than subsequent stages (i.e., enrolling and starting the first session) since messages were delivered at this point in the recruitment pipeline.…”
Section: Minimal Effect Of Culturally Informed Message Features (Aim 1)supporting
confidence: 69%
“…The difference in model-predicted rates of site clicks between the best performing message feature (9.5% for the testimonials message) compared to the poorest performing message feature (6.2% for the somatization message) is slightly larger than those found in two previous studies conducted among Latinx individuals (1.11%; Barrera et al, 2014; . 03% Graham et al, 2012), but more than two times smaller than those found in two studies conducted among general samples (9.10%; Birnbaum et al, 2017;8.71%;Silverman et al, 2023). While small, differences of this size could be potentially meaningful (in terms of attracting thousands of more individuals to visit the DMHI website for no extra cost) if marketing materials were scaled to reach millions of Spanish-speaking Latinx individuals, which becomes possible when using targeted social media marketing.…”
Section: Minimal Effect Of Culturally Informed Message Features (Aim 1)mentioning
confidence: 64%
See 3 more Smart Citations